Luminal Toxin-Binding Agents for Clostridium difficile Infection. (August 2016) - McCoy, Ryan M.; Klick, Andrew; Hill, Steven; Dull, Ryan B.
Objective: To systematically search the literature for trials evaluating luminal toxin-binding agents (LTBAs) for Clostridium difficile infection (CDI). Methods: A systematic search was conducted utilizing PubMed and International Pharmaceutical Abstracts with the following terms: anion-exchange resins, C difficile, cholestyramine, tolevamer, and colestipol . Articles were included if published in the English language and reported clinical outcomes of more than 5 adult humans with CDI treated with LTBAs. Results: Nearly all clinical trials evaluated LTBA as monotherapy for CDI and LTBAs are inferior to standard therapy. In contemporary practice, LTBAs are employed as adjunctive or sequential therapy for which there is a paucity of data. Some data suggest potential efficacy for recurrent CDI. Current guidelines for CDI assert LTBAs are contraindicated due to drug–drug interactions with vancomycin. However, the impact of this interaction on clinical outcomes has not been evaluated, and it is unknown whether higher doses of vancomycin or separating the administration of LTBAs from vancomycin would mitigate this interaction. Conclusion: LTBA monotherapy is inferior to vancomycin and metronidazole for CDI. Some data indicate possible benefit in reducing recurrent CDI, but outcomes with adjunctive and/or sequential LTBAs are unavailable. Further studies are needed to investigate the role of LTBAs for CDI.